Technology and Conceptual Art in Fashion Shows and Designs by Iris Van Herpen - Al-Shareef, Dalal Abdullah Al-Harthy (Arab Journal for Sciences and Research Publishing, 2021)
The research aims to study the role of technology and conceptual art in enriching and distinguishing Iris Van Herpen designs through analysis of display information, expressive input (source of inspiration - concept - artistic vision), performance. The plastic and technological methods and treatments that the designer undertook in those shows. The research followed the descriptive and analytical approach according to the method of content analysis, by preparing a list to analyze the content of eleven of the most prominent and important fashion shows of Iris van Herpen from (2010) to (2020). A set of performance methods and plastic and technological treatments have been reached through which fashion shows, technical designs and applied scientific research can be constructed for the results of this research. The results showed that fashion designer Van Herpen was able to combine technology with conceptual art in fashion designing for her seasonal shows through expressive entries and her collaborations with individuals from other disciplines. The researcher also extracted some technical characteristics of the costume designer Herpen as an artistic conceptual school in the field of fashion and fashion. The research recommended holding workshops and supervising research teams aiming to present experiences and explorations in the field of fashion design that combine multiple disciplines. Designers are encouraged to implement designs that link fashion design to postmodern arts and display them in art galleries and art museums